Puberty induction in young gilts: ovarian, uterine, and pregnancy responses - Guo, J.; Grieger, David M.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The age of gilts when their first litter is produced affects reproductive efficiency and the applications of biotechnologies such as in vitro fertilization and genetic engineering. Therefore, we evaluated the effect of age on response to puberty induction in gilts. Gilts were injected with PG600® followed 96 h later with human chorionic gonadotropin to induce follicular growth and ovulation, respectively. In the first experiment, 84-, 104-,124-, 144-, and 164-d-old gilts were used. For treated gilts, uterine weight, uterine length, number of corpora lutea (CL), peripheral progesterone (P4), and estradiol (~) increased (P < .05) linearly with age. Uterine luminal prostaglandins (PGs) PGE and PGF decreased for gilts treated at 124 d of age or older. The second experiment evaluated pregnancy success for gilts induced to ovulate at 116 vs 151 d of age. The effects of induction of two consecutive estrous cycles also were evaluated. Two of seven (28.6%) and four of nine (44.4%) gilts first treated when 116 and 151 d old but none of seven gilts treated at both 96 and 116 d of age were pregnant 60 d postinseillination. Results indicated that induction of a prior cycle did not inlprove pregnancy rates. However, some gilts in this population maintained pregnancies to 60 d when induced to ovulate and inseminated at 120 d of age.
Keywords: Swine; Puberty; Induction; Gonadotropin treatment; Gilt